Towards inclusive collaboration in volcanology: guidelines for best-engagement protocols in international collaboration - IAVCEI-INVOLC International Network for Volcanology Collaboration (Springer, 2024)
The International Network for Volcanology Collaboration (INVOLC) is a network formalised by the International Association of Volcanology and Chemistry of the Earth’s Interior (IAVCEI) with the specific ambition to enhance volcanology globally through improved international collaboration. IAVCEI-INVOLC was created with a focus on volcano scientists working in resource-constrained contexts, including those based in low- or middle-income countries. After a community-wide online survey and inaugural workshop during which INVOLC’s ambitions were discussed, a series of challenges, as commonly experienced by those working in resource-constrained settings, were identified. These challenges may present barriers to participation in volcano science in an international context and are related to both organisational resources (financial, human, technical) and inclusion in research collaborations. In this perspectives paper, we present a series of 15 guidelines for best-engagement protocols in international collaboration in volcanology that may be adopted during times of quiescence, volcanic unrest and/or an eruption and its aftermath. Our aspiration is that these guidelines will help build more respectful, equitable and sustainable partnerships that will ultimately advance the science of volcanology.